SAP BEETLES (COLEOPTERA: NITIDULIDAE) IN FIELDS OF WILD STRAWBERRY FRAGARIA VESCA LINNAEUS IN THE LOCATIONS OF AUCALLAMA, BARRANCA AND SUPER, HUARAL IN LIMA, PERU - Gutiérrez-Bustamante, Silvia (2020)
In strawberry cultivation with traditional technology, nitidulides cause a minimum decrease in post-harvest due to being associated with overripe fruits. Nitidulids were collected during December 2018 and January 2019, in fi elds in the district of Aucallama (Huaral) and Supe (Barranca), Peru. A total of 54 individuals, 2 subfamilies, two genera and two species were recorded and determined. Th e species with the highest incidence was Lobiopa insularis (Castelnau, 1840), with 81% of specimens collected. Th e other registered species were: Carpophilus hemipterus, Carpophilus sp.1 and Carpophilus sp.2.